Aerobic Exercise Reduce Blood Glucose in Type 2 Diabetes Mellitus - Roni Sianturi; Akhmad Mustofa (Universitas Muhammadiyah Semarang, 2022)
Diabetes mellitus type 2 is a metabolic disease caused by disruption of insulin action and characterized by hyperglycemia. Management of type 2 diabetes mellitus needs to be done to achieve optimal glycemic control to prevent various complications. Aerobic exercise walking is a way to lower blood glucose that is easy for people with type 2 diabetes mellitus. Determine the effect of aerobic exercise in lowering blood glucose in people with type 2 diabetes mellitus. The study is a literature review with the PICOC method for searching articles on databases such as Pubmed, Science Direct, Cochrane Library, and Proquest. The articles that were reviewed were limited to 2015-2020 and the types of research were quasi-experiments and randomized control trials. Seven articles match in criteria, four international articles and three national articles. Analysis of the articles showed that the characteristics of respondents were 49-65 years old, 209 men, 191 women, the average duration of type 2 diabetes mellitus was 5.3-9 years and the average HbA1C value was 6.4% - 8.4%. Glucose value in the research article showed a decrease in various glucose indicators such as HbA1C, capillary glucose, fasting glucose, and continuous glucose monitoring. Aerobic exercise in the frequency of seven days to 25 weeks with moderate to vigorous intensity, 15-60 minutes of exercise time/session, and the type of exercise is walking on a treadmill, walking 10,000 steps/day, and brisk walking. Aerobic walking exercise can lower blood glucose and is easily done by people with type 2 diabetes mellitus.